LOYALITAS PELANGGAN DITINJAU DARI KUALITAS PELAYANAN LIFESTYLE DAN TRUST (STUDI KASUS SALON JOHNNY ANDREAN THE PARK MALL) - Devi Ayu Prihatining Tyas (JURNAL ILMIAH EDUNOMIKA, 2020)
The service industry is currently experiencing a very significant development for example Beauty salon services. The greater the interest of consumers visiting the salon, the more rapid one's business will start a salon services business. In the research process with the aim of determining and explaining the quality of service, lifestyle, trust in Jonny Andrean's salon purchasing decisions. The sample processing technique uses accidental samples with a sample size of 100 respondents. Research using quantitative research. The analysis method uses multiple linear regression. The results of this study are the variables of service quality, lifestyle, trust together or simultaneously have a significant effect on Jonny Andrean's salon purchasing decisions. service quality, lifestyle and persial trust significantly influence purchasing decisions and explained the quality of service, lifestyle, trust 31.7%. Keywords: purchase decision, service quality, lifestyle, trust